Synergistic Effect of Cinnamon Essential Oil (Cinnamomum burmannii) and Doxorubicin on T47D Cells Correlated with Apoptosis Induction - Etyk Yunita Anjarsari; Nita Kristina; Yonika Arum Larasati; Dyaningtyas Dewi Pamungkas Putri; Edy Meiyanto (Indonesian Journal of Cancer Chemoprevention, 2013)
Cinnamon  (Cinnamomum burmannii)  shows  anticancer activity  in  several  types  of  cancer  cells.  The aim of this study is to  observe the  cytotoxic  activity  of  cinnamon essential oil (CEO) solely and its combination with doxorubicin,  also the  ability  of  the  combination to induce apoptosis on T47D breast cancer cells. The CEO was prepared through distillation of dry cinnamon bark. Cytotoxic  assay  was performed by using MTT assay and apoptosis determination was done by using double staining with ethidium bromide and acridine orange. The result showed that CEO exhibited cytotoxic effect on T47D cells with IC50 values of 75 µg/ml.  Moreover, CEO showed synergist effect with doxorubicin. The lowest combination index (CI) with CI values of 0,37 was obtained by combination of doxorubicin-CEO  37,5  µg/ml-1,25  µM.  Treatment with CEO solely and its combination with doxorubicin showed apoptosis induction on T47D cells. The results of this  study  indicate  the potency of CEO  to  be  developed  as co-chemotherapeutic  agent  of  doxorubicin on breast cancer. Keywords:  cinnamon essential oil, doxorubicin, T47D cells, combination cytotoxic